Influenza virus A H5N1 and H1N1 : features and zoonotic potential (2011)
ABSTRACT: Influenza A viruses which belong to the Orthomyxoviridae family, are enveloped, pleomorphic, and contain genomes of 8 single-stranded negative-sense segments of RNA. Influenza viruses have three key structural proteins: hemagglutinin (HA), neuraminidase (NA) and Matrix 2 (M2). Both HA and NA are surface glycoproteins diverse enough that their serological recognition gives rise to the traditional classification into different subtypes. At present, 16 subtypes of HA (H1-H16) and 9 subtypes of NA (N1- N9) have been identified. Among all the influenza A viruses with zoonotic capacity that have been described, subtypes H5N1 and H1N1, have shown to be the most pathogenic for humans. Direct transmission of influenza A viruses from birds to humans used to be considered a very unlikely event but its possibility to spread from human to human was considered even more exceptional. However, this paradigm changed in 1997 after the outbreaks of zoonotic influenza affecting people from Asia and Europe with strains previously seen only in birds. Considering the susceptibility of pigs to human and avian influenza viruses, and the virus ability to evolve and generate new subtypes, that could more easily spread from pigs to humans, the possibility of human epidemics is a constant menace. A recent example was the outbreak of H1N1 influenza in 2009 that crossed species and geographical borders affecting up to 20 to 40% of the people in some parts of the world. Vaccines and control measures are continuously being developed to address a threat that every year claims human and animal lives, and makes us fear for a new and more lethal strain of the virus.